Ownership governance, institutional pressures and circular economy accounting information disclosure. Issue 3 (29th July 2014) - Y. Li, Eldon; Wang, PuCha; Che, Fei; Fan, ShanShan; Gu, Chen
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – This paper aims to explore the determinants of circular economy accounting information disclosure quality, and also to make empirical analysis on the relationship between circular economy accounting information disclosure quality and corporate ownership governance and institutional pressures according to institutional theory and corporate governance theory. Finally, this paper provides some corresponding suggestions for heightening circular economy accounting information disclosure quality. Design/methodology/approach – This paper constructs enterprise circular economy accounting information disclosure model with Chinese characteristics. First, it takes disclosure index method to measure enterprise circular economy accounting information disclosure quality, followed by the hypotheses of this study. Then, this study employs a statistical analysis technique to empirically study the relationship between enterprise circular economy accounting information disclosure quality and ownership governance and institutional pressures, to study the ways to heighten enterprise circular economy accounting information disclosure quality in Chinese background. Findings – Ownership governance and institutional pressures mainly determine quality of circular economy accounting information disclosure. This paper draws the following conclusions: Chinese listed companies have heightened their circular economy accounting information disclosure quality due to ownership concentration, shareholding of institutional investors, mandatory disclosure, capital structure and assets size. However, the circular economy accounting information disclosure quality has low correlation with the profitability and the location of listed companies. Originality/value – Both in China and the West, few scholars or experts adopt empirical research to study the determinants of circular economy accounting information disclosure quality in an institutional theory and corporate governance theory perspective based on China's supervisory system background. This paper makes a thorough analysis of the factors that affect listed companies' circular economy accounting information disclosure quality, and provides some corresponding suggestions relevant for heightening circular economy accounting information disclosure quality.